An intronic SNP affects skeletal muscle development by regulating the expression of TP63 - Chen, Yufen; Wang, Zhen; Qu, Xiaolu; Song, Bangmin; Tang, Yueting; Li, Bugao; Cao, Guoqing; Yi, Guoqiang (Frontiers in Veterinary Science, 2024)
Background Porcine skeletal muscle development is pivotal for improving meat production. TP63, a transcription factor, regulates vital cellular processes, yet its role in skeletal muscle proliferation is unclear. Methods The effects of TP63 on skeletal muscle cell viability and proliferation were investigated using both mouse and porcine skeletal muscle myoblasts. Selective sweep analysis in Western pigs identified TP63 as a potential candidate gene for skeletal muscle development. The correlation between TP63 overexpression and cell proliferation was assessed using quantitative real-time PCR (RT-qPCR) and 5-ethynyl-2’-deoxyuridine (EDU). Results The study revealed a positive correlation between TP63 overexpression and skeletal muscle cell proliferation. Bioinformatics analysis predicted an interaction between MEF2A, another transcription factor, and the mutation site of TP63. Experimental validation through dual-luciferase assays confirmed that a candidate enhancer SNP could influence MEF2A binding, subsequently regulating TP63 expression and promoting skeletal muscle cell proliferation. Conclusion These findings offer experimental evidence for further exploration of skeletal muscle development mechanisms and the advancement of genetic breeding strategies aimed at improving meat production traits.